2021
DOI: 10.1038/s41598-021-95401-z
|View full text |Cite
|
Sign up to set email alerts
|

Lateral hypothalamus involvement in control of stress response by bed nucleus of the stria terminalis endocannabinoid neurotransmission in male rats

Abstract: The endocannabinoid neurotransmission acting via local CB1 receptor in the bed nucleus of the stria terminalis (BNST) has been implicated in behavioral and physiological responses to emotional stress. However, the neural network related to this control is poorly understood. In this sense, the lateral hypothalamus (LH) is involved in stress responses, and BNST GABAergic neurons densely innervate this hypothalamic nucleus. However, a role of BNST projections to the LH in physiological responses to stress is unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Sympathetically mediated vasoconstriction of cutaneous beds during aversive threats reduces skin temperature ( Blessing, 2003 ; Vianna and Carrive, 2005 ). Therefore, the drop in tail skin temperature during restraint was measured as an indirect measure of the sympathetic response to cutaneous beds ( Oliveira et al, 2015 ; Gomes-de-Souza et al, 2021 ). Measurements of tail skin temperature were performed at 5 and 0 min before restraint for basal values; 5, 10, 20, 40, and 60 min during restraint, as well as 10, 20, 30, 40, 50, and 60 min during the recovery phase ( Benini et al, 2019 ; Barretto-de-souza et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sympathetically mediated vasoconstriction of cutaneous beds during aversive threats reduces skin temperature ( Blessing, 2003 ; Vianna and Carrive, 2005 ). Therefore, the drop in tail skin temperature during restraint was measured as an indirect measure of the sympathetic response to cutaneous beds ( Oliveira et al, 2015 ; Gomes-de-Souza et al, 2021 ). Measurements of tail skin temperature were performed at 5 and 0 min before restraint for basal values; 5, 10, 20, 40, and 60 min during restraint, as well as 10, 20, 30, 40, 50, and 60 min during the recovery phase ( Benini et al, 2019 ; Barretto-de-souza et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The procedures for the assessment of Fos-positive cells were as previously described ( Gomes-de-Souza et al, 2021 ). Briefly, 90 min after the onset of the restraint stress (i.e., 30 min following the termination of the restraint stress session), the rats were anesthetized (urethane, 1.2 g/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, injection of a GPR18 agonist into the RVLM increased HR [ 215 ]. HR was increased following microinjection of AEA into the dorsal periaqueductal grey (dPAG; [ 217 , 218 , 219 ]) but decreased upon microinjection of an inhibitor of AEA degradation into the bed nucleus of the stria terminalis (BNST; [ 222 , 223 , 224 ]); both effects were mediated via CB 1 -Rs.…”
Section: Tachycardia—mechanismsmentioning
confidence: 99%
“…As well as affecting appetite in healthy weight individuals, anxiety is also strongly related to eating disorders including anorexia nervosa. Imaging studies have shown an altered cerebellar network connectivity in anorexia nervosa patients compared to healthy controls, in particular increased activity within the vermis [178,179,180]. The disorder is associated with altered food-cue processing and decreased appetite upon presentation of food cues [172,181,182].…”
Section: The Influence Of Negative Emotions On Eatingmentioning
confidence: 99%